Morphological features of fascia lata in relation to fascia diseases. (1st November 2016) - Szotek, Sylwia; Dawidowicz, Joanna; Eyden, Brian; Matysiak, Natalia; Czogalla, Aleksander; Dudzik, Grzegorz; Leśniewicz, Anna; Maksymowicz, Krzysztof
ABSTRACT: Fascia lata is an important element of the fascial system, which forms the continuum of connective tissue throughout the body. This deep fascia envelops the entire thigh and hip area and its main function is to transmit mechanical forces generated by the musculoskeletal system of the lower extremities. Fascia lata is also known as a useful and easily harvested graft material. Despite its crucial role in lower extremity biomechanics and wide-ranging applications in plastic and reconstructive surgery, both the structure of fascia lata and particularly the cells populating this tissue are relatively unexplored and therefore poorly understood. The aim of this study was to characterize the main cell populations encountered within human fascia lata and to try to understand their role in health and diseases. Pathologically unchanged human fascia lata was obtained post mortem from adult males. The specimens were analyzed under light, electron, and confocal microscopy. On the basis of different visualization techniques, we were able to characterize in detail the cells populating human fascia lata. The main cells found were fibroblasts, fibrocytes, mast cells, cells showing myoid differentiation, nerve cells, and most interestingly, telocytes. Our results supplement the formerly inadequate information in the literature regarding the cellular components of deep fascial structure, may contribute to a better understanding of the pathogenesis of fascial disorders and improve fascia lata application as a graft material.